Analisis Jaringan Pipa Distribusi Air Minum Di Kabupaten Rokan Hilir Menggunakan Software EPANET 2.0 - Muhamad Gifari; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bangko Pusako, Rimba Melintang, and Tanah Putih Tanjung Melawan district in Rokan Hilir regency rely on water sources that are not guaranteed in quality such as borehole water, as well as rainwater, bottled water, and jerry cans which are not guaranteed in quantity. Community water needs reach 312.5 L/s for the next 20 years (2036), so it is necessary to analyze water supply network using EPANET 2.0 software. The simulation results show that the hydraulic conditions of the piping for the entire planning area at peak hours have a velocity of 0.02-1.85 m/s, a pressure of 8.99-66.20 m, and the highest unit headloss is 8.46 m/km.Keywords: EPANET 2.0, piping, simulation